1984
DOI: 10.1111/j.1432-1033.1984.tb08289.x
|View full text |Cite
|
Sign up to set email alerts
|

Guanine‐nucleotide‐dependent inhibition of adenylate cyclase of rabbit heart by glucagon

Abstract: The present study demonstrates an inhibitory effect of glucagon on the adenylate cyclase system of rabbit heart. Data suggest that glucagon receptors can interact with both the activatory and inhibitory guanine-nucleotidebinding proteins and the physical state of membranes may play a role in determining which interaction will be preferential

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 49 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…Consistent with the formation of cAMP after glucagon stimulation in rats, the efficacy or potency of glucagon in the rat ventricle to raise contractility was increased by adding theophylline (an unselective PDE inhibitor [69]; rolipram a PDE4 inhibitor, [84] or cilostamide, a PDE 3 inhibitor, [85]). Consistent with the lack of a glucagon-induced positive inotropic effect in the rabbit heart, glucagon did not increase the AC activity in preparations from rabbit hearts [66].…”
Section: Signal Transductionsupporting
confidence: 72%
See 2 more Smart Citations
“…Consistent with the formation of cAMP after glucagon stimulation in rats, the efficacy or potency of glucagon in the rat ventricle to raise contractility was increased by adding theophylline (an unselective PDE inhibitor [69]; rolipram a PDE4 inhibitor, [84] or cilostamide, a PDE 3 inhibitor, [85]). Consistent with the lack of a glucagon-induced positive inotropic effect in the rabbit heart, glucagon did not increase the AC activity in preparations from rabbit hearts [66].…”
Section: Signal Transductionsupporting
confidence: 72%
“…Glucagon elevates, in the isolated atria of dogs, cats, and guinea pigs, but not in rabbits, the force of contraction [3]. Consistent with the lack of a glucagon-induced positive inotropic effect in the rabbit heart, glucagon did not increase the AC activity in preparations from rabbit hearts [66]. Species differences occur, which makes it challenging to translate animal data to the situation in patients directly.…”
Section: Speciesmentioning
confidence: 97%
See 1 more Smart Citation
“…From the comparative kinetic data for CAMP generation after VIP and forskolin, it is therefore likely that both receptor desensitization and CAMP-PDE activation coincide with the transient rise in CAMP levels evoked by VIP in enterocyte-like cells incubated in the absence of IBMX (fig.2, expt.3). Secondly, it has been shown that the physical state of the plasma membrane (lipid microviscosity) may promote inhibition or stimulation by a hormone via either the Ni or the N, structures of the cyclase [24]. For example, Robberecht et al [25] have shown that short-chain alcohols inhibited forskolin-stimulated rat cardiac adenylate cyclase, probably by interacting with lipids and altering membrane fluidity.…”
Section: Discussionmentioning
confidence: 99%